ADULTS WITH TYPE 2 DIABETES MELLITUS AND RENAL INSUFFICIENCY IN ABSENCE OF ALBUMINURIA AND RETINOPATHY - Ali Thamir Rashed; Samer Ahmed Abbas; Rafid Thair Habeeb (Web of Journals Publishing, 2025)
The kidney damage caused by type 2 diabetes mellitus (T2DM) is more varied than that of type 1 diabetic mellitus (T1DM). People with type 2 diabetes don't always get classical diabetic glomerulosclerosis, which is marked by a drop in the glomerular filtration rate (GFR), albuminuria, and retinopathy. If the estimated glomerular filtration rate (eGFR) is less than 60 mL/min per 1.73 m² of body surface area (BSA), then the person has chronic renal insufficiency.
Keywords: albuminuria, , retinopathy, type 2 diabetes mellitus, Renal Insufficiency